Orchestrating climate justice: the model for a new geopolitical era (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2025)
It reflects on climate justice from the perspective of a new geopolitical era, highlighting the asymmetry between developed and developing countries, with a focus on the challenges faced by urban centers in the era of the climate emergency.(Received: September 2025 | Accepted: November 2025)
Keywords: Climate Justice; Geopolitics; Global Inequality; Urban Centers; Climate Emergency